1986
DOI: 10.1002/1097-0142(19860415)57:8<1522::aid-cncr2820570814>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Production of plasminogen activator by a primary HSV-2-induced hamster fibrosarcoma and itsin vivo derived sublines

Abstract: The plasminogen activator (PA) content of a primary HSV-2-induced hamster fibrosarcoma and sublines derived from its in vivo metastases was investigated using the indirect 125I-labeled fibrin plate method. Fresh tissue culture lines established from primary HSV-2-333-2-26 tumors were shown to produce levels of PA similar to sublines derived from lung or kidney foci that developed after resection of primary tumors. In comparison, normal hamster embryo fibroblast (NHEF) and baby hamster kidney cells produced lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Attachment to the basement membrane is a prerequisite to dissolution of the extracellular matrix (Liotta et al, 1977) and experiments performed in vitro have demonstrated tumour cell binding to the basement membrane using laminin as the attachment factor (Terranova et al, 1982). We have, therefore, assessed the influence of BM components, and lung fibroblasts, on the secretion of type IV collagenase in sublines and clone of defined metastatic ability in the hamster tumour model (Walker et al, 1982;Teale et al, 1983Teale et al, ,1984Khidair et al, 1986). The secretion of plasminogen activator (PA), a serine protease capable of degrading serum plasminogen converting it to plasmin, which in turn is capable of degrading fibrin and laminin (Carlson et al, 1984;Liotta et al, 1981), was also investigated in this system.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…Attachment to the basement membrane is a prerequisite to dissolution of the extracellular matrix (Liotta et al, 1977) and experiments performed in vitro have demonstrated tumour cell binding to the basement membrane using laminin as the attachment factor (Terranova et al, 1982). We have, therefore, assessed the influence of BM components, and lung fibroblasts, on the secretion of type IV collagenase in sublines and clone of defined metastatic ability in the hamster tumour model (Walker et al, 1982;Teale et al, 1983Teale et al, ,1984Khidair et al, 1986). The secretion of plasminogen activator (PA), a serine protease capable of degrading serum plasminogen converting it to plasmin, which in turn is capable of degrading fibrin and laminin (Carlson et al, 1984;Liotta et al, 1981), was also investigated in this system.…”
supporting
confidence: 77%
“…PA induces the activation of plasminogen giving rise to plasmin which has been associated with the ability of tumour cells to metastasize (Carlson et al, 1984;Wang et al, 1980) possibility by its ability to degrade laminin (Liotta et al, 1981). We have previously shown that the hamster tumour cell lines used here are able to recrete PA but no correlation between the level of PA secretion and the metastatic profile was found (Khidair et al, 1986). We are now able to report that the addition of laminin, fibronectin or type IV collagen to the tumour cell lines failed to alter the expression of plasminogen activator activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations